STRATEGI KOMUNIKASI PEMASARAN SEA FOREST ADVENTURE NUVASA BAY PT. SINAR MAS LAND BATAMMELALUI MEDIA SOSIAL - Hidayah, Nurul; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Nowadays communication becomes an important thing in marketing because it can strengthen the strategy of marketing of Sea Forest Adventure Nuvasa Bay by PT. Sinar Mas Land. Sea Forest Adventure is a program from Nuvasa Bay Batam where is a place to play and have vacation with family. This place previously who named as Palm Spring has transformed into a modern tourist attraction with additional facilities and expanded the play area. As one of the vacation place, Sea Forest Adventure Nuvasa Bay PT. Sinar Mas Land also has some competitors who engaged in the same field, so it need some strategy to achieve the goal to knowing the marketing strategy of communication that Sea Forest Adventure Nuvasa Bay PT. Sinar Mas Land, and to find out Segmentation, Targeting, Positioning and Social Media that used by Sea Forest Adventure.This research uses descriptive qualitative method, which is collecting the data and obtained based on the reality of the data in the field through the observation, interviews and documentation. The informants in this research were: one (1) of HR Manager member, one (1) of Sales Manager Coordinator, two (2) of marketings, one (1) of ticketing, one (1) of marketing communication, and four (4) visitors to support this research. The data analysis is usedthe interactive model by Huberman and Miles, this technique is for checking the validity of data through triangulation and the extension of participation.The results showed that the marketing strategy communication of Sea Forest Adventure Nuvasa Bay PT. Sinar Mas Land was done by using segmentation, targeting and positioning strategies. It also refers to the 4P marketing with mix concept, namely : Product, Price, Place and Promotion. Sea Forest Adventure products provide some rides who divided into 3 namely : Water Adventure, Lamd Adventure and Multi fanction Yards. Water adventure consists of Aqua Track Adventure, jet ski, banana boat, knee boarding, canoe and ,mangrove tour. Sea forest adventure provides promo package which there are two rides combined that is more cheaper than buying a ticket with just one ride. The location of Sea Forest Adventure is located on Jl.Hang Lekui Nongsa sub-district which is located faraway from the urban areas so itâ€™s suitable for a vacation. The staff of Sea Forest Adventure has promotes this place through various way such as social meida and brochures. The social media that used by Sea Forest Adventure are instagram and facebook.Â Keywords : forest marketing communication strategy,through social media